Association between childbirth attitudes and fear on birth preferences of a future generation of Australian parents - Hauck, Yvonne; Stoll, K.; Hall, W.; Downie, Jill (Elsevier BV, 2016)
Background: The reality of childbirth fear is recognised for expectant parents but we lack knowledge about the childbirth attitudes of the next generation of Australian parents. Aim: Examination of adults' attitudes toward childbirth including influencing contributing factors, fear scores, birth preferences and reasons for this preference. Methods: A cross-sectional online study was conducted with 654 Western Australian students attending one tertiary institution. Students (male and female) were eligible to participate if they were less than 40 years of age and did not currently have children but confirmed their intention to become parents. To assess associations or comparison of means, bi-variable analyses (Chi square test, Fisher's Exact test, Independent Student's t-test or one way ANOVA) were used. Factors associated with childbirth fear and birth preferences were assessed with binary logistic regression analysis. Findings: Childbirth attitudes were shaped by family members' (82.0%) and friends' experiences (64.4%) plus media (TV, YouTube, and movies) (63.5%). Furthermore, 15.6% of adults indicated a preference for a caesarean birth, even without obstetric complications. Likewise, 26.1% reported elevated fear; students with elevated fear scores had 2.6 times greater odds of wanting a caesarean birth. Only 23.4% of students felt confident about their childbirth knowledge. Conclusion: Adults reported fear levels that warrant attention prior to a future pregnancy. Although the majority would choose a vaginal birth, they require awareness of benefits and risks for both vaginal and caesarean births to ensure their decisions reflect informed choice rather than influences of inadequate knowledge or fear.